2012
DOI: 10.6018/analesps.28.3.155981
|View full text |Cite
|
Sign up to set email alerts
|

Problemas de Conducta y Depresión entre Refugiados no Acom-pañados: La asociación entre el impacto del trauma pre-migratorio y la aculturación

Abstract: Título: Problemas de Conducta y Depresión entre Refugiados no Acompañados: La asociación entre el impacto del trauma pre-migratorio y la aculturación Resumen: Hay escaso conocimiento sobre la adaptación a largo plazo de los niños menores de edad que emigran sin ser acompañados por sus padres para pedir asilo en un país extranjero. El presente estudio investigó los efectos combinados del impacto de haber tenido experiencias traumáticas relacionadas con la guerra antes de emigrar y los índices del proceso de acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
1
10
0
3
Order By: Relevance
“…Perceived lower levels of discrimination mediated this effect. The same study, and others, also found an association between acculturation-specific difficulties and depression [ 37 , 42 ]. These findings confirm the stated reciprocal relations between sociocultural adaptation and social contacts and relations in the host country .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Perceived lower levels of discrimination mediated this effect. The same study, and others, also found an association between acculturation-specific difficulties and depression [ 37 , 42 ]. These findings confirm the stated reciprocal relations between sociocultural adaptation and social contacts and relations in the host country .…”
Section: Discussionsupporting
confidence: 58%
“…Several international studies confirm the influence of sociocultural adaptation on the mental health of UMRs. The study of [ 42 ] reported that depression decreases when the level of cultural competence increases. Perceived lower levels of discrimination mediated this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since traumatic experiences and acculturation processes might affect depressive symptoms (Oppedal and Idsoe, 2012;LeMaster et al, 2017), the interaction between trauma and acculturation strategies might be a crucial factor. Consistent with this assumption, a previous study (Ngo et al, 2001) observed variation in the effect of pre-migration traumatic experiences on depression in migrants according to the level of acculturation.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies such as those of Jiménez [52] argued that we cannot understand individuals from such groups without stopping to comprehend their inner self. Other authors added to this the importance of an inter-cultural education for the full socio-cultural integration and mental health of this population [53].…”
Section: Discussionmentioning
confidence: 99%